2019
DOI: 10.1039/c8sm02491j
|View full text |Cite
|
Sign up to set email alerts
|

Formation of phase separated vesicles by double layer cDICE

Abstract: Here we present a modified version of cDICE that allows incorporation of cholesterol into lipid bilayers and enables the reproducible formation of phase-separated vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In the original cDICE paper, 28 as well as in other follow-up studies, 29 , 30 , 36 , 37 injection capillaries were pulled from glass tubes to final orifice diameters of a maximum of 20 μm. Since we found these narrow glass capillaries to be a significant source of experimental variation and problems due to easy clogging of the orifice, we instead used commercially available fused silica capillary tubing with larger diameters (25, 50, and 100 μm) to allow for more consistent results, as previously used by Litschel et al ( 33 ) We found that using all three capillary sizes, our chloroform-based lipid-in-oil dispersion and optimized workflow led to high yields of GUVs with a mean diameter of 12 μm and coefficient of variation of 47% for a capillary size of 100 μm and rotation speed of 1900 rpm ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%
“…In the original cDICE paper, 28 as well as in other follow-up studies, 29 , 30 , 36 , 37 injection capillaries were pulled from glass tubes to final orifice diameters of a maximum of 20 μm. Since we found these narrow glass capillaries to be a significant source of experimental variation and problems due to easy clogging of the orifice, we instead used commercially available fused silica capillary tubing with larger diameters (25, 50, and 100 μm) to allow for more consistent results, as previously used by Litschel et al ( 33 ) We found that using all three capillary sizes, our chloroform-based lipid-in-oil dispersion and optimized workflow led to high yields of GUVs with a mean diameter of 12 μm and coefficient of variation of 47% for a capillary size of 100 μm and rotation speed of 1900 rpm ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that the lipid composition of vesicles did not vary with their size, we made careful choices about how we produced vesicles. Because different techniques incorporate different ratios of lipids into vesicles (25)(26)(27), we produced all vesicles by the same technique: electroformation (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…While the droplet crosses the interfaces of oil and water, it is step-wise coated with both leaflets of a lipid bilayer, and emerges as a unilamellar vesicle of the size of the initial droplet. [357] In 2019, Durre and Bausch [358] described a loading variant of cDICE to introduce cholesterol into lipid bilayers, enabling reliable formation of phase-separated vesicles. Another interesting variant was developed by Morita et al [359] It produces cell-sized liposomes of well-controlled lipid composition by means of droplet-shooting and size-filtration in a centrifuge.…”
Section: Microfluidics-based Techniques To Fabricate Protocellsmentioning
confidence: 99%